Diabetic macular edema - Marks, Steven J; Hale, Benjamin P (Nepalese Journal of Ophthalmology, 2016)
Diabetic retinopathy is a frequent manifestation of long standing diabetes mellitus. According to the World Health Organization diabetes affects nine percent of the adult population worldwide (Diabetes Fact Sheet, 2015). Of all of the common diseases of the eye, diabetic retinopathy has a great impact on the working age population and therefore presents a huge socioeconomic burden in all areas of the world.